Palladium on Carbon‐Catalyzed Aqueous Transformation of Primary Alcohols to Carboxylic Acids Based on Dehydrogenation under Mildly Reduced Pressure. Issue 6 (24th March 2015) - Sawama, Yoshinari; Morita, Kosuke; Asai, Shota; Kozawa, Masami; Tadokoro, Shinsuke; Nakajima, Junichi; Monguchi, Yasunari; Sajiki, Hironao
Abstract The catalytic dehydrogenation of alcohols to carbonyl products is a green sustainable oxidation with no production of waste except for hydrogen, which can be an energy source. Additionally, a reusable heterogeneous catalyst is valuable from the viewpoint of process chemistry and water is a green solvent. We have accomplished the palladium on carbon (Pd/C)‐catalyzed dehydrogenation of primary alcohols to carboxylic acids in water under a mildly reduced pressure (800 hPa). The reduced pressure can be easily controlled by the vacuum controller of the rotary evaporator to remove the excess of generated hydrogen, which causes the reduction (reverse reaction) of aldehydes to alcohols (starting materials) and other undesirable side reactions. The present method is applicable to the reaction of various aliphatic and benzylic alcohols to the corresponding carboxylic acids, and the Pd/C could be reused at least 5 times. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>